ENTREPRENEURIAL ECOSYSTEMS: HOW LOCALIZED SUPPORT SYSTEMS FOSTER INNOVATION AND ECONOMIC DEVELOPMENT IN EMERGING MARKETS - Maria Costa (Modern American Journals, 2025)
In recent years, the concept of entrepreneurial ecosystems has gained significant attention as a key driver of innovation, economic growth, and social development, particularly in emerging markets. Entrepreneurial ecosystems are interconnected networks of actors, institutions, and resources that facilitate the creation, growth, and scaling of entrepreneurial ventures. This paper examines how localized support systems within entrepreneurial ecosystems foster innovation and contribute to economic development in emerging markets. By analyzing the roles of key ecosystem components such as government policies, access to capital, mentorship, infrastructure, and education, the paper explores how these elements work together to nurture entrepreneurship in developing economies. Case studies from countries like India, Brazil, and Kenya highlight the impact of localized support systems in creating sustainable entrepreneurial ventures. The paper also identifies challenges such as lack of access to finance, regulatory constraints, and infrastructural limitations, and provides recommendations for fostering a conducive environment for entrepreneurship.
Keywords: Entrepreneurial Ecosystems, Innovation, Economic Development, Emerging Markets, Localized Support Systems, Startups, Entrepreneurship, Access to Capital, Mentorship, Government Policy.